2020
DOI: 10.1039/c9dt03914g
|View full text |Cite
|
Sign up to set email alerts
|

Azo-triazolide bis-cyclometalated Ir(iii) complexes via cyclization of 3-cyanodiarylformazanate ligands

Abstract: Sterically encumbered iridium-bound formazanate ligands undergo redox-neutral cyclization to form azo-triazolides, a new class of redox-active chelating ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 66 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…We note that complex 1, which contains an eutralf ormazan coordinated to iridium through the pyridine, is the most difficult to oxidize in the series, whereas in the rest of the compounds, with formally monoanionic metal-bound formazanate cores the oxidation waves are cathodically shifted. We have previously shown that the HOMO in platinum [29] and iridium [33] formazanate compounds is majority formazanate-centered with minor metal 5d contribution, thus we believe that the oxidation involves both the formazanate and the metal. Interestingly,t he oxidation wave in complex 1 has ah igherc urrent value than the reduction wave, suggesting that in this compound where the formazanatei snot chelated to the metal concurrent oxidation of the formazanate and the [Ir(F 2 ppy) 2 ] + fragment may be occurring.…”
Section: Electrochemistrymentioning
confidence: 81%
See 3 more Smart Citations
“…We note that complex 1, which contains an eutralf ormazan coordinated to iridium through the pyridine, is the most difficult to oxidize in the series, whereas in the rest of the compounds, with formally monoanionic metal-bound formazanate cores the oxidation waves are cathodically shifted. We have previously shown that the HOMO in platinum [29] and iridium [33] formazanate compounds is majority formazanate-centered with minor metal 5d contribution, thus we believe that the oxidation involves both the formazanate and the metal. Interestingly,t he oxidation wave in complex 1 has ah igherc urrent value than the reduction wave, suggesting that in this compound where the formazanatei snot chelated to the metal concurrent oxidation of the formazanate and the [Ir(F 2 ppy) 2 ] + fragment may be occurring.…”
Section: Electrochemistrymentioning
confidence: 81%
“…Apart from intense peaks in the UV (l < 350 nm) attributed to localized p!p*t ransitions of the aryl substituents from both C^N and formazanate, an otable absorption between 460 nm and 700 nm stands out among all compounds,w hich is assigned as a p!p*t ransition within the formazanate framework with as mall amount of metal-to-ligand charge transfer (MLCT) character,o nt he basis of many other platinum and iridium formazanates previously studied experimentally and computationally. [29][30][31]33] The two free formazans have similar UV/Vis absorption wavelengths, with the low-energy transition occurring 482 nm in Fza and 466 nm in Fzb.C oordination through the 4-pyridyl substituent of Fza,a so bserved in complex 1,h as am inimal effect on the absorption wavelength, which occurs at nearly identicalw avelength (483 nm) in this complex. When the formazanate chelates the metal center, as observed in most other complexes,weo bserve as izeable red-shift of the p!p*t ransition, as we have previously noted in studying many other Pt and Ir formazanates.…”
Section: Uv/vis Absorption Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…10 Our group has expanded the coordination chemistry of formazanates to third-row transition metals with a series of heteroleptic cyclometalated platinum complexes and biscyclometalated iridium complexes, [29][30][31] and accessed homoleptic azo-iminate platinum complexes and azo-1,2,3triazolide iridium complexes via hydrogenative cleavage or [3+2] cyclization of formazanates, respectively. 32,33 Compared to the numerous formazanate complexes where a single metal atom is chelated within the NNCNN framework, polynuclear compounds involving formazanates remain rare. Access to complex polynuclear formazanate complexes is desirable for a number of reasons; in addition to greatly expanding the fundamental coordination chemistry of formazanates, there is the possibility of designing compounds with enhanced or unusual redox, magnetic, or photophysical properties, enabled by electronic communication between the building blocks mediated by the redox-active formazanate.…”
Section: Introductionmentioning
confidence: 99%